Travel journal for a trip to Europe, 1838-1839 - Van Buren, John, 1810-1866. ([S.l.])
1 online resource
Keywords: John Van Buren's 'Travel journal for a trip to Europe, 1838-1839' is a record of the a year he spent in England, Scotland, Ireland, Belgium and Holland, primarily for his father, Martin Van Buren, the 8th President of the United States. A fly-on-the-wall view of the political and social situation in Europe was invaluable to the President at a highly sensitive moment in Anglo-American relations, and provides a rich and insightful view for historians of the period. Published in its entirety for the first time, Van Buren's objective and good-humoured observations present fresh insights into complex and compelling personalities and relationships on both sides of the Atlantic, providing an invaluable and highly readable resource for scholars and students of the period, as well as for the general reader.